2013
DOI: 10.1088/1612-2011/11/1/015102
|View full text |Cite
|
Sign up to set email alerts
|

Tunable dual-wavelength actively Q-switched Er/Yb double-clad fiber laser

Abstract: We demonstrate experimentally a dual-wavelength tunable actively Q-switched fiber laser using 3 m of Er 3+ /Yb 3+ co-doped fiber as the gain medium. For wavelength tuning we used a tunable Hi-Bi FBG having two reflection wavelengths separated by 0.4 nm. The laser emits a dual-wavelength signal that is tunable in a range of 11.8 nm. Laser operation can be switched between single and double wavelength emission. The laser operates at repetition rates from 30 to 110 kHz with pulse durations of 280 ns and pulse ene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 20 publications
1
14
1
Order By: Relevance
“…The high-power efficiency slope in CW operation of 38%, as it can be expected, exhibits advantages of the use of EYDCF as a gain medium in fiber lasers operating in the 1.55 µ m waveband. Compared with the previously reported investigations of actively Q-switched EYDCF lasers in which the laser linewidth is around 200 pm [5,13,17,18], the obtained linewidth was narrowed to 73 pm. The Q-switched laser operation shows stable pulse trains in a high repetition rate in a wide range from 90 to 270 kHz, which represents an improvement compared with the low and narrow range of repetition rate from the reported investigations where the maximum repetition rate in which stable Q-switched pulses is around 140 kHz with a maximum repetition rate range of ~100 kHz [5].…”
Section: Resultscontrasting
confidence: 85%
See 2 more Smart Citations
“…The high-power efficiency slope in CW operation of 38%, as it can be expected, exhibits advantages of the use of EYDCF as a gain medium in fiber lasers operating in the 1.55 µ m waveband. Compared with the previously reported investigations of actively Q-switched EYDCF lasers in which the laser linewidth is around 200 pm [5,13,17,18], the obtained linewidth was narrowed to 73 pm. The Q-switched laser operation shows stable pulse trains in a high repetition rate in a wide range from 90 to 270 kHz, which represents an improvement compared with the low and narrow range of repetition rate from the reported investigations where the maximum repetition rate in which stable Q-switched pulses is around 140 kHz with a maximum repetition rate range of ~100 kHz [5].…”
Section: Resultscontrasting
confidence: 85%
“…The unconnected port of the AOM (output 2) is used to measure the laser average output power by a thermal power sensor (Thorlabs S146C, 900-1650 nm, 20 W) (Thorlabs Inc., Newton, NJ, USA) and a power meter console (Thorlabs PM100D) (Thorlabs Inc., Newton, NJ, USA). besides what has been reported by our investigation group [5,13,17], Zhang et al [18] reported an allfiber actively Q-switched ring cavity fiber laser based on Er/Yb co-doped fiber which demonstrated the improvement of power efficiency when EYDCF is used, however, the pulsed operation reported is in a narrow and low repetition rate range from 10 to 25 kHz. In this paper, we experimentally demonstrate a simple and compact actively Q-switched fiber laser operating in the 1550 nm waveband.…”
Section: Methodssupporting
confidence: 47%
See 1 more Smart Citation
“…Therefore, the use of double-clad doped fibers provides a stable and straightforward method to generate high energy nanosecond pulses in actively Q-switched dual-wavelength fiber lasers. From reported investigations, EYDCF offers high conversion efficiency for high-energy pulses generation [44,45].…”
Section: Q-switched Fiber Lasers: a Review From Operating Principle Tmentioning
confidence: 99%
“…Nowadays, the use of double clad rare-earth doped fibers (DCF) are attractive on fiber amplifiers and laser systems designs due to their advantages such as achieving of high power, heat dissipation and beam quality generation making then useful to generate Q-switched laser pulses. Currently, simultaneous dual-wavelength pulsed lasers have been of interest due their potential applications in THz generation research and spectral analysis, among others [12][13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%